1999
DOI: 10.1080/152165499307431
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Chicken Muscle Ecto-ATPase in Mammalian COS Cells

Abstract: Chicken muscle ecto-ATPase has unusual enzyme kinetics and properties not found in many other E-type ATPases. To determine whether the unique properties of the chicken ecto-ATPase are inherent in the protein sequence and not mediated by some unique property of the chicken system, we have spliced together two partial cDNAs encoding the ecto-ATPase. The enzymatic properties of the COS (green monkey kidney) cell-expressed protein are indistinguishable from the purified chicken gizzard ecto-ATPase, including a 2- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The majority of the enzymes hydrolysing ATP prefer Mg 2+ –ATP complex as a substrate [3]. NTPDase2 derived from chicken gizzard smooth muscle was activated the most strongly by Mg 2+ [36], whereas NTPDase1 from human placenta most efficiently hydrolysed ATP in the presence of Ca 2+ [37]. Our results indicate that the complexes Mg 2+ –ATP or Mn 2+ –ATP are preferred as substrate by synaptosomal NTPDases, while in the case of ADP, the Ca 2+ –ADP complexes are hydrolysed most effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the enzymes hydrolysing ATP prefer Mg 2+ –ATP complex as a substrate [3]. NTPDase2 derived from chicken gizzard smooth muscle was activated the most strongly by Mg 2+ [36], whereas NTPDase1 from human placenta most efficiently hydrolysed ATP in the presence of Ca 2+ [37]. Our results indicate that the complexes Mg 2+ –ATP or Mn 2+ –ATP are preferred as substrate by synaptosomal NTPDases, while in the case of ADP, the Ca 2+ –ADP complexes are hydrolysed most effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Native gel electrophoresis of COS cell-expressed chicken (20) and human ecto-ATPases (eNTPDase2) revealed that both enzymes had virtually the same mobility on a 6% acrylamide native gel, as judged by gel blot detection of the proteins after transfer to PVDF membrane (data not shown). However, because mobility in native gels is determined both by charge and size, we also determined the apparent size of the digitonin-solubilized ecto-ATPase by size-exclusion gel chromatography.…”
Section: Oligomeric Size Analysis Of Digitonin-solubilized Entpdasesmentioning
confidence: 97%
“…Transfected COS cell membranes (or rabbit skeletal transverse tubule membranes containing ecto-ATPase [20]) at 0.1 mg/ mL total protein were solubilized by adding digitonin to a nal concentration of 1% and mixing for 10 min at room temperature. The insoluble proteins were separated by centrifugation and the soluble proteins were applied to either a native Laemmli gel (no SDS was used, but the gel contained 0.1% digitonin; see [6]) or to a Sephacryl S-300 column equilibrated in a solution of 20 mM MOPS and 5 mM MgCl 2 , pH 7.4, containing 0.1% digitonin.…”
Section: Solubilization Native Gel Electrophoresis and Size-exclusimentioning
confidence: 99%
“…Stimulation of the avian enzyme by lectin was shown to occur through direct binding of the lectin to oligosaccharide residues, which might form part of the ecto-ATPase structure, because after desialylation no activation with wheatgerm agglutinin was observed and α-methylmannoside prevented stimulation by Con A [5,6]. Furthermore, glycosylation is crucial for chicken muscle ecto-ATPase, because expression of the enzyme in mammalian cells in the presence of tunicamycin resulted in an inactive, unfolded protein [31].…”
Section: Oligomeric Statementioning
confidence: 99%